2020
DOI: 10.1534/g3.120.401244
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian and Machine Learning Models for Genomic Prediction of Anterior Cruciate Ligament Rupture in the Canine Model

Abstract: Anterior cruciate ligament (ACL) rupture is a common, debilitating condition that leads to early-onset osteoarthritis and reduced quality of human life. ACL rupture is a complex disease with both genetic and environmental risk factors. Characterizing the genetic basis of ACL rupture would provide the ability to identify individuals that have high genetic risk and allow the opportunity for preventative management. Spontaneous ACL rupture is also common in dogs and shows a similar clinical presentation and progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
3
5
0
Order By: Relevance
“…The genome-based selection enables early recruitment of breeding candidates and hence, potentially reducing generation time in striped catfish as expected to reduce at least a half of generation interval in dairy cattle ( Hayes et al 2009 ). Our results are consistent with those reported in farmed animal ( Baker et al 2020 ), livestock ( González-Recio and Forni 2011 ; Li et al 2018 ), and plants ( Montesinos-López et al 2018 , 2019 ; Zingaretti et al 2020 ). Despite the superiority of the machine learning methods ( i.e.…”
Section: Discussionsupporting
confidence: 92%
“…The genome-based selection enables early recruitment of breeding candidates and hence, potentially reducing generation time in striped catfish as expected to reduce at least a half of generation interval in dairy cattle ( Hayes et al 2009 ). Our results are consistent with those reported in farmed animal ( Baker et al 2020 ), livestock ( González-Recio and Forni 2011 ; Li et al 2018 ), and plants ( Montesinos-López et al 2018 , 2019 ; Zingaretti et al 2020 ). Despite the superiority of the machine learning methods ( i.e.…”
Section: Discussionsupporting
confidence: 92%
“…The genomic selection can also shorten the breeding cycle of striped catfish as expected to reduce at least a half of generation interval in dairy cattle (Hayes et al 2009). Our results are consistent with those reported in farmed animal (Baker et al 2020), livestock (Li et al 2018; González-Recio and Forni 2011) and plants (Montesinos-López et al 2019; Montesinos-López et al 2018; Zingaretti et al 2020). Despite the superiority of the machine learning methods (i.e., ML-KAML) to PBLUP, GBLUP and ssGBLUP, they had similar predictive power to BayesR for both traits in our study.…”
Section: Discussionsupporting
confidence: 93%
“…The GBLUP method assumes that each marker has a genetic effect on the target trait, while the BayesC approach assumes that only some markers have a genetic effect on the trait. The results in this study indicated that the average prediction accuracy from cross-validation was not significantly different between GBLUP and BayesC in CHD and RCCL, which is consistent with previous studies ( Zhu et al, 2012 ; Sánchez-Molano et al, 2014 ; Sánchez-Molano et al, 2015 ; Baker et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%